Unmanned aerial vehicle motor fixing base - DING XU; LIU JIA; LI DAN; SI LIZHENG (2018)
The utility model relates to an unmanned aerial vehicle motor fixing base installs the one end of unmanned aerial vehicle's cantilever, the housing comprises an upper housing and a lower housin, go upto form after the casing is fixed with the lower mutual lock of casing and be used for pegging graft the inserting groove of cantilever, cantilever one end is pegged graft and is fixed in the inserting groove, unmanned aerial vehicle's rotor motor fixed mounting is in go up on the casing. The utility model discloses a set up casing and lower casing, fix the fixing base on the cantilever, make things convenient for installation of self and fixing of rotor motor. 本实用新型涉及种无人机电机固定座，安装在所述无人机的悬臂的端；包括上壳体和下壳体，所述上壳体和下壳体相互扣合固定后形成用于插接所述悬臂的插接槽，所述悬臂端插接固定在所述插接槽内，所述无人机的旋翼电机固定安装在所述上壳体上。本实用新型通过设置上壳体和下壳体，将固定座固定在悬臂上，方便自身的安装和旋翼电机的固定。